(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The formation of dental hard tissues is a metabolically dependent process closely related to the general health status of the organism during prenatal and early postnatal development. Disturbances in mineral metabolism, deficiencies of vitamins and trace elements, as well as endocrine disorders may significantly affect the processes of amelogenesis and dentinogenesis. This narrative review summarizes current evidence on the role of metabolic factors in the development of pathological changes in enamel and dentin, discusses pathogenetic mechanisms, and highlights their clinical relevance for dental practice.